2016
DOI: 10.1007/s10654-016-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal alcohol binge-drinking in the first trimester and the risk of orofacial clefts in offspring: a large population-based pooling study

Abstract: Using individual participant data from six population-based case–control studies, we conducted pooled analyses to examine maternal alcohol consumption and the risk of clefts among >4600 infants with cleft lip only, cleft lip with cleft palate, or cleft palate only and >10,000 unaffected controls. We examined two first-trimester alcohol measures: average number of drinks/sitting and maximum number of drinks/sitting, with five studies contributing to each analysis. Study-specific odds ratios (ORs) were estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
(31 reference statements)
0
27
1
3
Order By: Relevance
“…The model also adjusted for any maternal alcohol consumption and use of folic-acid-containing supplements in the first trimester, and age (≤18, 19–25, 26–30, 31–35, and ≥36 years), an indicator for low maternal education (incomplete high school versus higher education), and dummy variables representing the 6 contributing studies. These study-specific fixed effects account for differences among the study populations in oral cleft risk factors, prevalence, time effects, and case-to-control ratios (1, 3, 21). These fixed effects, as well as the balancing of cases and controls by year of birth within each study, ensured that time is not a confounder in the pooled analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The model also adjusted for any maternal alcohol consumption and use of folic-acid-containing supplements in the first trimester, and age (≤18, 19–25, 26–30, 31–35, and ≥36 years), an indicator for low maternal education (incomplete high school versus higher education), and dummy variables representing the 6 contributing studies. These study-specific fixed effects account for differences among the study populations in oral cleft risk factors, prevalence, time effects, and case-to-control ratios (1, 3, 21). These fixed effects, as well as the balancing of cases and controls by year of birth within each study, ensured that time is not a confounder in the pooled analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for maternal alcohol consumption as a risk factor is less consistent, although consuming large amounts over a short period of time (e.g. “binge drinking”) appears to increase risk 14 . Broad measures, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2 According to some studies, alcohol consumption can inhibit retinoic acid production, increasing the risk of CL/P. 6,7 Smoking during pregnancy apparently doubles the risk of orofacial cleft in newborns. Moreover, in vitro studies have shown that tobacco inhibits palatal fusion and affects cell proliferation, leading to medial edge epithelial cell death.…”
Section: Introductionmentioning
confidence: 99%